2005
DOI: 10.1073/pnas.0505537102
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary population genetics of promoters: Predicting binding sites and functional phylogenies

Abstract: We study the evolution of transcription factor-binding sites in prokaryotes, using an empirically grounded model with point mutations and genetic drift. Selection acts on the site sequence via its binding affinity to the corresponding transcription factor. Calibrating the model with populations of functional binding sites, we verify this form of selection and show that typical sites are under substantial selection pressure for functionality: for cAMP response protein sites in Escherichia coli, the product of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
128
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 109 publications
(136 citation statements)
references
References 28 publications
7
128
1
Order By: Relevance
“…We obtain a moderate level of selection 2N⌬F 0 ϭ [6 Ϫ 9] (the lower bound uses all loss events as defined in Methods, and the upper bound, the ones with only point mutations). This is comparable to the selection pressure previously found for Crp binding sites in Escherichia coli (16). Thus, conservation of sites is not complete: functional binding sites in the last common ancestor remain functional in all four species in 65-94% of the cases.…”
Section: Epistasis and Compensatory Mutationsmentioning
confidence: 50%
See 3 more Smart Citations
“…We obtain a moderate level of selection 2N⌬F 0 ϭ [6 Ϫ 9] (the lower bound uses all loss events as defined in Methods, and the upper bound, the ones with only point mutations). This is comparable to the selection pressure previously found for Crp binding sites in Escherichia coli (16). Thus, conservation of sites is not complete: functional binding sites in the last common ancestor remain functional in all four species in 65-94% of the cases.…”
Section: Epistasis and Compensatory Mutationsmentioning
confidence: 50%
“…The average selective advantage of a site with given energy over mutants with different energy defines a fitness landscape (18), which can be inferred from energy histograms of functional sites and background sequence as shown in ref. 16. In the spirit of this model, we identify functional sites by evolutionary conservation of energy rather than sequence.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This hypothesis lacks quantitative evidence so far, but a number of recent studies have found fitness effects in noncoding DNA. Transcription factor binding sites in bacteria are under substantial selection for functionality (13), and putative regulatory regions in eukaryotes also show substantial selective constraints (14,15). Evidence of positive selection has been reported for intergenic DNA in Drosophila (16,17), albeit with near-neutral selection coefficients (17).…”
mentioning
confidence: 99%